Dose–response relationship between physical activity and cardiometabolic risk in obese children and adolescents: A pre-post quasi-experimental study - Chen, Zekai; Zhu, Lin (Frontiers in Physiology, 2023)
Objective: This study aims to explore the dose-response relationship between the daily duration of moderate to vigorous physical activity (MVPA) and the improvement of cardiometabolic risk (CMR) indicators in obese children and adolescents. Methods: Seventy-seven obese children and adolescents aged 10–17 years were randomly recruited for a 4-week exercise intervention in a closed camp during 2019 to 2021, physical activity was monitored by ActiGraph GT3X+ to obtain daily MVPA duration, and the improvement of CMR indicators were reflected by the changes () of waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), fasting insulin (FINS), fasting plasma glucose (FPG), and homeostasis model assessment of insulin resistance (HOMA-IR) before and after the intervention, calculated as “+indicator” = values after intervention – values before intervention. The groups were divided into different doses of Q1~Q3 according to the daily MVPA duration from low to high. The differences in the improvement of different dose groups were compared by one-way analysis of covariance (ANCOVA), and the dose-response relationship between MVPA duration and CMR indicators improvement was analyzed by linear regression and piecewise regression. The nonlinear relationship was analyzed by restricted cubic spline (RCS). Results: (1) Compared with indicators before the intervention, WC, SBP, DBP, TC, TG, HDL-C, LDL-C, FINS, and HOMA-IR were significantly lower after the intervention (P value<0.05). (2) The dose-response relationship between MVPA and LDL-C improvement was non-linear (P-Nonlinear<0.05). When MVPA > 77.1min/day, LDL-C further decreased with the increase of MVPA duration [β=-0.013, 95% confidence interval (CI): -0.013, -0.005], and when MVPA ≤ 77.1min/day, increasing the MVPA duration did not increase the improvement of LDL-C. Conclusion: There was a nonlinear dose-response relationship between the daily MVPA duration and LDL-C improvement in obese children and adolescents. In order to obtain more significant improvement in LDL-C through increased MVPA duration, MVPA duration should be higher than 77.1 min/day.